Changes in breathing, swallowing and tongue position during treatment with functional elastic appliance in conjunction with myotherapy in the group of patients with malocclusion before growth spurt - Urbaniak-Malinowska, Gabriela; Niżankowska-Jędrzejczyk, Agata; W. Loster, Bartłomiej (Journal of Stomatology, 2017)
Introduction. Many activities such as chewing, swallowing, breathing, and speech, whose normal or abnormal functioning has a very significant impact on the development of dento-facial complex take place within the masticatory system. Numerous studies conducted on preschool children show a close correlation between the occurrence of abnormal function and maxillofacial complex defects on the one hand and the presence of malocclusions on the other. One of the most common dysfunctions is a dysfunction of the tongue, which is related to abnormal swallowing, and dysfunction related to mouth breathing.. Many researchers have noted a close correlation between the tongue or breathing dysfunction and the occurrence of certain malocclusions. The most common are: open bite, distoclusion, mesioclusion, and cross bite. Malocclusion resulting from dysfunction can be treated by eliminating the disorders of the surrounding structures and by enabling their proper development. That is why it is important to eliminate these abnormal facial muscle dysfunctions and to enable the normal development of the dental arches as soon as possible. The earlier the return to correct function, the easier and faster, even spontaneously without orthodontic appliance therapy, the revocation of malocclusion formed on the background of dysfunction will be possible. Aim of the study. To analyse changes in breathing, swallowing and tongue position during treatment with standard functional elastic appliance with appropriate muscle exercises in children with the specified malocclusion (open bite, Class II/1) and dysfunction before peak of growth spurt. Material and method. Clinical trials were conducted in a group of ten patients aged 6 to 10 years, with milk or mixed dentition, before peak of growth spurt with the presence of at least one of the impaired functions of breathing, swallowing, and/or an abnormal position of the tongue during swallowing and with identified partial front open bite (overbite minimum of –2 mm) or Class II /1 malocclusion. The treatment consisted of the use of elastic functional appliance series EF Evolution of Orthoplus to re-educate the disturbed functions of swallowing and/or breathing. Results. After the treatment was completed all the patients reported improvement in competence of lips and in type of breathing. All children also noticed improvement in orbicular oris function during swallowing and its balance when closing the lips (no more excessive muscle contraction when trying to close the mouth) was reported by all study subjects. Significant changes among all patients in the activity of swallowing were noted. After re-education was completed in all the children with Class II/1, the tongue (during swallowing) could touch the lingual ridge of the maxillary alveolar process. Little or no improvement was noted in overbite dimension and tongue function in patients with skeletal open bite, which confirms the principle that in this group of patients tongue thrusting is the act of adaptation to the existing malocclusion, and it is necessary to ensure the front seal.